If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2y = 3y + 3y + -9 + -7 Reorder the terms: 4 + -2y = -9 + -7 + 3y + 3y Combine like terms: -9 + -7 = -16 4 + -2y = -16 + 3y + 3y Combine like terms: 3y + 3y = 6y 4 + -2y = -16 + 6y Solving 4 + -2y = -16 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 4 + -2y + -6y = -16 + 6y + -6y Combine like terms: -2y + -6y = -8y 4 + -8y = -16 + 6y + -6y Combine like terms: 6y + -6y = 0 4 + -8y = -16 + 0 4 + -8y = -16 Add '-4' to each side of the equation. 4 + -4 + -8y = -16 + -4 Combine like terms: 4 + -4 = 0 0 + -8y = -16 + -4 -8y = -16 + -4 Combine like terms: -16 + -4 = -20 -8y = -20 Divide each side by '-8'. y = 2.5 Simplifying y = 2.5
| 4(3-4x)=-56 | | 49m^3-m=0 | | 22/3-(9-32/3)=82/3-11 | | 84.245x=537 | | 64=6x+2x+8 | | x+y+8=0 | | -8/3w=7 | | -x^2-7x-36=0 | | 6x+2-7x=3 | | -6/x+3=7 | | 3/4/2/3 | | 5/6=x+1/9 | | 3/4/2/3-3/4 | | 4-4x=-16 | | -7(2+x)=-42 | | 4(-2+5x)=32 | | 4+5x-3x=24 | | T+5=75-6t | | y-1/20=13/20 | | 53/4-15/4 | | 4(-8n-3)+4n=-6(5n-3) | | -6(x+3)-15=13+8 | | 8x^3-18x^2-2x+3=0 | | f(x)=x+3 | | 1250x+1000=1450x+1000 | | 3n+3=240 | | 24x^3-9x^2-18x=3x | | F^2+33f=0 | | 4x-9+5x=72 | | x/3-x=4 | | 131/4-33/4 | | 3n+6=126 |